Optimal design and grasp ability evaluation of four-finger tendon-driven hand. (22nd December 2017) - Yan, Wenyu; Nie, Hong; Chen, Jinbao; Han, Dong
Since human hands have complex anatomical structure and are hard to be duplicated, lots of researches have been done to simplify it by gesture analysis, functional workspace evaluation and many other approaches. In this article, a novel light-duty four-finger hand driven by tendons is presented. The design is based on principal components analysis theory in order to reduce the minor degrees of freedom and lower the mechanism complexity. Meanwhile, optimization of the structure parameters is carried out with respect to the analyses of grasp ability and the single finger's dexterity. A few simple and explicit indices are defined to evaluate the hand properties. In addition, this article also discusses the tendon routing method to realize the accuracy control of the tendon-driven hand's joints. The approach presented in this article can be easily implemented on other mechanical hand platforms and assist the grasp planning in further works.